2013
DOI: 10.1016/j.wear.2012.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Wear of CoCrMo alloys used in metal-on-metal hip joints: A tribocorrosion appraisal

Abstract: a b s t r a c tA good biocompatibility, excellent mechanical properties and high corrosion resistance characterize CoCrMo alloys. Therefore they are widely used for artificial joints in biomedical implants. However, the degradation of the implants during service life leads to the release into the body of toxic ions and wear particles. This continuous degradation is of concern for long-term stability of the implants. Published literature has highlighted the relevance of lubrication as well as metallurgical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(134 citation statements)
references
References 86 publications
(147 reference statements)
8
126
0
Order By: Relevance
“…For these reasons, we can conclude that the multilayer coating provides protection from pitting and general corrosion. The surface semiquantitative analysis of the pit area A selected is described in section 3.5. passive film on the sample surface was locally removed thus exposing bare metal to the solution and therefore the rubbed areas experienced an increase in metal oxidation rate because the loss of passivity [7]. Furthermore, an important surface degradation on the CoCrMo substrate is observed on the wear rate, as is shown in Figure 10.…”
Section: Corrosionmentioning
confidence: 98%
See 2 more Smart Citations
“…For these reasons, we can conclude that the multilayer coating provides protection from pitting and general corrosion. The surface semiquantitative analysis of the pit area A selected is described in section 3.5. passive film on the sample surface was locally removed thus exposing bare metal to the solution and therefore the rubbed areas experienced an increase in metal oxidation rate because the loss of passivity [7]. Furthermore, an important surface degradation on the CoCrMo substrate is observed on the wear rate, as is shown in Figure 10.…”
Section: Corrosionmentioning
confidence: 98%
“…Tribocorrosion, defined as the conjoint action of any mechanical wear under load and corrosive attack of the material surface [6], has been shown to shorten the life of prostheses. Moreover, corrosion during reciprocating movement is accelerated by the synergistic effect of the wear [7]. This phenomenon is highly relevant to the field of biomedical joint implants in general, and specifically to hip and knee joints [7,8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1) CoCr-MOM bearings exhibit extremely high survival rates over 510 years of service 2,3) owing to their excellent mechanical properties and extremely low wear rate, 47) and they are expected to serve for longer life than the present ones for younger, active patients. Despite of these encouraging results, recent reports also indicated that unexpected high failure rates for large head MOM bearings and debris detachment from the rubbing surfaces, which led to an alert from the Medicines and Healthcare products Regulatory Agency prompting an urgent review of all MOM articulations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of these encouraging results, recent reports also indicated that unexpected high failure rates for large head MOM bearings and debris detachment from the rubbing surfaces, which led to an alert from the Medicines and Healthcare products Regulatory Agency prompting an urgent review of all MOM articulations. 8) The debris enter the blood, serum, and urine of recipients, cause a high incidence of adverse reaction to metal debris (ARMD) 3,911) known as periprosthetic soft tissue reactions and systemic genotoxicity.…”
Section: Introductionmentioning
confidence: 99%